Two-sample Mendelian randomization to study the causal association between gut microbiota and atherosclerosis - Jiang, Shijiu; Yu, Cheng; Lv, Bingjie; He, Shaolin; Zheng, Yuqi; Yang, Wenling; Wang, Boyuan; Li, Dazhu; Lin, Jibin (Frontiers in Immunology, 2024)
Background According to some recent observational studies, the gut microbiota influences atherosclerosis via the gut microbiota-artery axis. However, the causal role of the gut microbiota in atherosclerosis remains unclear. Therefore, we used a Mendelian randomization (MR) strategy to try to dissect this causative link. Methods The biggest known genome-wide association study (GWAS) (n = 13,266) from the MiBioGen collaboration was used to provide summary data on the gut microbiota for a two-sample MR research. Data on atherosclerosis were obtained from publicly available GWAS data from the FinnGen consortium, including cerebral atherosclerosis (104 cases and 218,688 controls), coronary atherosclerosis (23,363 cases and 187,840 controls), and peripheral atherosclerosis (6631 cases and 162,201 controls). The causal link between gut microbiota and atherosclerosis was investigated using inverse variance weighting, MR-Egger, weighted median, weighted mode, and simple mode approaches, among which inverse variance weighting was the main research method. Cochran’s Q statistic was used to quantify the heterogeneity of instrumental variables (IVs), and the MR Egger intercept test was used to assess the pleiotropy of IVs. Results Inverse-variance-weighted (IVW) estimation showed that genus Ruminiclostridium 9 had a protective influence on cerebral atherosclerosis (OR = 0.10, 95% CI: 0.01–0.67, P = 0.018), while family Rikenellaceae (OR = 5.39, 95% CI: 1.50–19.37, P = 0.010), family Streptococcaceae (OR = 6.87, 95% CI: 1.60–29.49, P = 0.010), genus Paraprevotella (OR = 2.88, 95% CI: 1.18–7.05, P = 0.021), and genus Streptococcus (OR = 5.26, 95% CI: 1.28–21.61, P = 0.021) had pathogenic effects on cerebral atherosclerosis. For family Acidaminococcaceae (OR = 0.87, 95% CI: 0.76–0.99, P = 0.039), the genus Desulfovibrio (OR = 0.89, 95% CI: 0.80–1.00, P = 0.048), the genus RuminococcaceaeUCG010 (OR = 0.80, 95% CI: 0.69–0.94, P = 0.006), and the Firmicutes phyla (OR = 0.87, 95% CI: 0.77–0.98, P = 0.023) were protective against coronary atherosclerosis. However, the genus Catenibacterium (OR = 1.12, 95% CI: 1.00–1.24, P = 0.049) had a pathogenic effect on coronary atherosclerosis. Finally, class Actinobacteria (OR = 0.83, 95% CI: 0.69–0.99, P = 0.036), family Acidaminococcaceae (OR = 0.76, 95% CI: 0.61–0.94, P = 0.013), genus Coprococcus2 (OR = 0.76, 95% CI: 0.60–0.96, P = 0.022), and genus RuminococcaceaeUCG010 (OR = 0.65, 95% CI: 0.46–0.92, P = 0.013), these four microbiota have a protective effect on peripheral atherosclerosis. However, for the genus Lachnoclostridium (OR = 1.25, 95% CI: 1.01–1.56, P = 0.040) and the genus LachnospiraceaeUCG001 (OR = 1.22, 95% CI: 1.04–1.42, P = 0.016), there is a pathogenic role for peripheral atherosclerosis. No heterogeneity was found for instrumental variables, and no considerable horizontal pleiotropy was observed. Conclusion We discovered that the presence of probiotics and pathogens in the host is causally associated with atherosclerosis, and atherosclerosis at different sites is causally linked to specific gut microbiota. The specific gut microbiota associated with atherosclerosis identified by Mendelian randomization studies provides precise clinical targets for the treatment of atherosclerosis. In the future, we can further examine the gut microbiota’s therapeutic potential for atherosclerosis if we have a better grasp of the causal relationship between it and atherosclerosis.